2022
DOI: 10.3389/fpsyg.2022.894220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of animated pedagogical agent-guided loving-kindness meditation on flight attendants’ spirituality, mindfulness, subjective wellbeing, and social presence

Abstract: Loving-kindness meditation (LKM) was first practiced by Buddhists and then developed by clinical psychologist. Previous studies on LKM have mainly focused on the impact of real person-guided meditation on depression, anxiety, and other negative psychology. During the COVID-19 pandemic, this study explored the effect and mechanism of media-guided LKM on the improvement of social presence, mindfulness, spirituality, and subjective wellbeing (SWB). From the viewpoint of positive psychology, this study compared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Previous research showed that mindfulness can have a positive impact on different populations. For example, increasing mindfulness among clinicians can improve the safety competence of medical staff (Braun et al, 2019 ), patients (Liu et al, 2022b ), employees (Liu et al, 2022c ), and flight attendants (Liu et al, 2022d , e ). It has also been demonstrated that mindfulness is an effective method for coping with COVID-19-related stress (Weis et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research showed that mindfulness can have a positive impact on different populations. For example, increasing mindfulness among clinicians can improve the safety competence of medical staff (Braun et al, 2019 ), patients (Liu et al, 2022b ), employees (Liu et al, 2022c ), and flight attendants (Liu et al, 2022d , e ). It has also been demonstrated that mindfulness is an effective method for coping with COVID-19-related stress (Weis et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the development of media technology, people are more and more accustomed to obtaining health-related information and knowledge from new media. Media technologies related to mindfulness and relevant research endeavors have increased markedly, as can be seen from the growing number of academic publications ( Terzimehić et al, 2019 ; Lukoff et al, 2020 ; Liu et al, 2022a ). These studies provided with diverse perspectives and foundations for investigating health information about mindfulness.…”
Section: Introductionmentioning
confidence: 99%
“…The use of eight service functions was measured; for example, “search (people, groups, official accounts),” “give a like, comment, dynamic publishing,” etc. ( Wei et al, 2011 ; Zhou, 2014 ; Liu et al, 2022d ). The responses ranged from “not at all” = 1 to “often” = 5 (M = 3.35, SD = 1.03, α = 0.89).…”
Section: Methodsmentioning
confidence: 99%